2015
DOI: 10.1160/th14-10-0852
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of histone and DNA methylation in human atherosclerotic carotid plaques

Abstract: Little is known about epigenetics and its possible role in atherosclerosis. We here analysed histone and DNA methylation and the expression of corresponding methyltransferases in early and advanced human atherosclerotic carotid lesions in comparison to healthy carotid arteries. Western Blotting was performed on carotid plaques from our biobank with early (n=60) or advanced (n=60) stages of atherosclerosis and healthy carotid arteries (n=12) to analyse di-methylation patterns of histone H3 at positions K4, K9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…Our results show that atherosclerosis patients presented lower genome-wide methylation level than in healthy controls, which is consistent with previous reports [ 9 , 21 ]. Our results further confirm that atherosclerosis occurrence is closely related to genome-wide methylation level reduction and that MTHFR C667T loci polymorphism was associated with AS occurrence.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results show that atherosclerosis patients presented lower genome-wide methylation level than in healthy controls, which is consistent with previous reports [ 9 , 21 ]. Our results further confirm that atherosclerosis occurrence is closely related to genome-wide methylation level reduction and that MTHFR C667T loci polymorphism was associated with AS occurrence.…”
Section: Discussionsupporting
confidence: 94%
“…DNA methylation is also related to AS [ 8 ]. Genome-wide methylation level was lower in AS patients [ 9 ] and affects atherosclerotic plaque formation in ApoE −/− mice [ 10 , 11 ]. Studies found that vascular smooth muscle cell genome DNA methylation level was regulated by Hcy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may cause detrimental effects, which are linked to epigenetic changes, e.g. in fibrotic lesions of myocardium and atherosclerotic arteries [ 188 , 190 , 191 ]. Recent epigenetic studies have clearly shown that the aging process is associated with significant changes in the chromatin landscape [ 192 - 194 ].…”
Section: Does Excessive Hif-1α Stimulation Disturb Chromatin Landscapmentioning
confidence: 99%
“…Recently, many studies have revealed that there are remarkable epigenetic changes in atherosclerotic vessels, e.g. reduced levels of H3K9me2,3 and H3K27me2,3 [ 190 , 191 ]. Epigenetic alterations have also been reported in cardiovascular diseases [ 202 ] as well as in obesity and metabolic syndrome [ 203 ].…”
Section: Does Excessive Hif-1α Stimulation Disturb Chromatin Landscapmentioning
confidence: 99%
“…For example, genomic DNA isolated from human atherosclerotic lesions was found to be hypomethylated [ 12 ]. Recently, our group demonstrated significant differences in histone and DNA methylation and the expression of corresponding methyltransferases at different stages of atherosclerosis in carotid arteries [ 13 ]. Krishna et al have hypothesized that epigenetic mechanisms may also play a role in the pathogenesis of AAA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%